An empirical model for the ballistic limit of bi-layer ceramic/metal armour - Serjouei, Ahmad (2014)
An empirical model to estimate the ballistic velocity limit (BLV) for ceramic/metal bi-layer armour materials is proposed by considering momentum and energy balance during impact process. Impact simulations of different combinations of various thicknesses and materials for front ceramic and backing metallic layers and different projectile lengths, chosen based on orthogonal array approach, are performed. Three ceramic materials as front layer, namely: alumina (Al2O3 AD96), boron carbide (B4C) and silicon carbide (SiC) and three materials as backing metallic layer, namely: aluminum alloy (Al 5083H116), steel 4340 and titanium alloy (Ti6Al4 V) are used in the parametric study. Empirical constants in the proposed model are obtained using least square fitting to the BLV data obtained from simulations. Comparison between proposed model results, for BLV of ceramic/metal armour impacted by flat-ended projectiles with available limited experimental data is carried out.